Law... fair or cost-effective? Considerations in the context of the right of ownership and liability rules in the Polish legal system - Zbąska-Caban, Olga (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
In the Polish literature the view that the law should be effective is present more and more frequently. Generally speaking, the effectiveness of law means ensuring the best possible functionality of regulations and legal institutions. As requested by Law & Economics, the law should seek to ensure social wealth. But are the actions to obtain economic outcomes fair, from the social point of view? The aim of the study is to answer this question basing on the selected topics of civil law. Such institutions as the right of ownership (including the consequences of its limitations presented on the example of the law of nuisance), the acquisitive prescription and liability rules in the Polish legal system have been subjected to considerations. The analysis demonstrated that the regulation of the civil institutions presented is cost effective, but not socially fair to the same extent. Evaluation of a regulation made ​​in terms of its effectiveness and usefulness may not be identical with the fundamental human ethical intuitions. The assumption that efficiency is an important goal of law, but it is not the only value which should be respected by the legal system is emphasised in the article, following the example of other authors. Therefore, the issues discussed, merely the acquisitive prescription is considered to combine equally the aspects of high-efficiency and justice. Additionally, in the study the advantages of the practical use of the vague phrases (such as the principle of socio-economic destination of law) have been highlighted. Thanks to the general clauses, law is adjusted to current needs and practices of the society, yielding the results which can be evaluated both as fair and cost-effective. On the other hand, the analysis of other issues discussed does not allow for such a clear evaluation. Although the law of nuisance and rules of liability can be considered effective in the economical aspects, they can not provide for a solution which is to the same extent fair and effective with respect to any potential situations that may occur in everyday life.
Keywords: Law and Economics; fairness of the law; social fairness; civil law; private law; social wealth; fair; justice; economic analysis of law; liability; usefulness; cost-effective; effectiveness of the law; efficiency